When makerspaces go mobile: case studies of transportable maker locations. Issue 4 (16th November 2015) - Moorefield-Lang, Heather Michele
Abstract : Purpose: – The purpose of this paper is to describe the implementation of mobile makerspaces in libraries and educational settings. Insights, decisions, challenges, and mobile makerspace projects will also be shared. Design/methodology/approach: – This paper delves into six case studies of librarians and educators who made the decision to go mobile with a makerspace. The case studies include public and school librarians, as well as educators in higher education settings. The author of this paper will describe the cases, projects, challenges, along with other aspects of implementing of a mobile makerspace. Findings: – Makerspaces, while becoming very popular in the field of librarianship, can be incredibly exciting to employ but often come with their own challenges and successes. What happens when the brick and mortar location is not enough? Librarians and educators begin to think creatively and bring the makerspace to the patrons if the clients cannot come to the space. Originality/value: – Currently the research on makerspaces is growing but there is still a limit to scholarly material in this field. When focussing on mobile makerspaces there are only blog posts and popular pieces. Nothing has been written on a wider range of case studies focussing on mobile makerspaces. This paper sets the foundation for further exploration in how librarians and educators can further serve patrons by making makerspaces mobile.